AN EMPIRICAL REVIEW ON THE GRADUATE ATTRIBUTES AND READINESS FOR EMPLOYABILITY AMONG THE ENGINEERING GRADUATES IN THE HIGHER EDUCATION INSTITUTIONS (HEIs) - Hinai, Masoud Rashid Al; Bhuiyan, Abul Bashar; Husin, Nor Azilah (Indian Journal of Finance and Banking, 2020)
The graduates’ readiness for employability has become a major issue for HEIs in the world due to growing concern from governments and industries on the quality of the graduates. As thus, this paper intends to determine the most required skills for Engineering graduate’s readiness for employability. Therefore, the main objective of the current study is to determine the skills required for Graduates’ Readiness for Employability for Engineering graduates. Specifically, this study intends to review the most current literature to specify the most required skills for the readiness of Engineering Graduates for Employability in the Higher Education Institutes (HEIs) in the world. The study reviews the current literature on graduates’ readiness for employability especially for engineering graduates as the main source of information. The study is designed to analyze and determine the engineering graduates’ readiness for employability required skills. The literature utilized for this study covers the latest literature (from 2014 to 2019) extracted from Google Scholar, ProQuest, and Scopus. The three main keywords used were ‘higher education’, ‘employability skills ‘or ‘readiness for employability skills, and ‘skills gap in the world. The study determines the engineering graduates’ readiness for employability required skills for the HEIs in the world. It analyses the most influential required skills for the graduate readiness for employability that will be considered as an empirical study on the graduates of the engineering colleges in the world. The study conceptualizes graduate readiness for employability requirements from the latest literature and papers. The results of the study will fill the gap in understanding the main required engineering graduates’ readiness for employability skills in the world. This study is intended to determine the most required graduates’ readiness for employability skills for engineering in the HEIs in the world. Besides, it will be used to advise a policy guideline for HEIs and researchers for the understanding of graduates’ readiness for employability skills requirements in the HEIs in the world.